2011
DOI: 10.1007/s10765-011-1097-5
|View full text |Cite
|
Sign up to set email alerts
|

Confirming Impurity Effect in Silver-Point Realization from Cell-to-Cell Comparisons

Abstract: As a continuation to earlier work on the silver-point realization, already reported at TEMPMEKO 2007, a new silver-point cell has been fabricated using 6N-nominal grade material that was analyzed by means of glow discharge mass spectrometry (GDMS) by the manufacturer. This new cell is evaluated by a direct cell comparison with one of the existing cells, which was also already reported at TEMP-MEKO 2007. One of those existing cells was drawn out from its crucible, and its ingot was analyzed by GDMS at four posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…For this zinc fixed-point cell, under all circumstances the agreement between the model and experiment improves as the distribution coefficient k → 0. This is consistent with other analyses which show that Raoult's law can be used to describe the effect of impurities on the freezing curve [7][8][9][10][11]. It was shown that the departure from the shape predicted by the numerical model towards the end of freezing could be explained by the fact that a significant amount of metal continues freezing elsewhere in the fixedpoint cell, after the metal immediately surrounding the SPRT sensing element has completely frozen.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For this zinc fixed-point cell, under all circumstances the agreement between the model and experiment improves as the distribution coefficient k → 0. This is consistent with other analyses which show that Raoult's law can be used to describe the effect of impurities on the freezing curve [7][8][9][10][11]. It was shown that the departure from the shape predicted by the numerical model towards the end of freezing could be explained by the fact that a significant amount of metal continues freezing elsewhere in the fixedpoint cell, after the metal immediately surrounding the SPRT sensing element has completely frozen.…”
Section: Discussionsupporting
confidence: 89%
“…The limitations of the analysis and knowledge of liquidus slopes, and whether the analysed sample is representative of the ingot in the fixed-point cell, make the SIE challenging to implement reliably in practice, and other methods are needed to provide supplementary evidence. Analysis of a series of measurements by Yamazawa et al [7][8][9][10] found that in most cases for Sn, Zn, Al and Ag fixed points, the corrections obtained from the freezing curve slope (assuming Raoult's law), SIE and direct cell comparison agreed well, even when the GDMS analysis indicated the presence of high k impurities, although in one case the SIE underestimated the magnitude of the correction relative to the other two methods by 30% [7,11]. Clearly Raoult's law, and other more general analyses of the freezing curve shape where k is not necessarily zero, remains useful.…”
Section: Introductionmentioning
confidence: 99%
“…The detected Co has the same value as the detection limit, so it could be less reliable. Ni was also found in our silver ingot [10] taken out from its crucible after being used so many times. This may reflect an imperfection of our cell fabrication facilities.…”
Section: In the Form Of Error Bars Showingsupporting
confidence: 52%
“…Considerable work has been performed on the effect of impurities in ITS-90 fixed points, utilising various correction methods on individual cells (Sn [4,5], Zn [6][7][8][9], Al [10] and Ag [11]) and in fixed point cells in general [12][13][14][15][16]. Two key methods have emerged, and are now recommended by the CCT, which are both based on a chemical assay of the metal to determine which impurities are present, and in what quantity.…”
Section: Introductionmentioning
confidence: 99%